Collapsibility and volume change behavior of unsaturated residual soil - Kim Huat, Bujang; Ali, Faisal; Choong, Foong Heng (Universiti Putra Malaysia Press, 2007)
Residual soils occur in most countries of the world but the greater areas and depths are normally found in tropical humid areas. In these places, the soil forming processes are still very active and the weathering is much faster than the erosive factor. Most residual exhibit high soil suctions for most of the year. The absence of positive pore water pressure except immediately after rain, renders conventional soil mechanics for saturated soil irrelevant. In particular, the effective stress theories of saturated soil are not applicable at the practical leve l. Ignorance or lack of understanding of the geotechnical behavior of soil in the partially or unsaturated state has caused a lot of damages to infrastructures, buildings and other structures. For instances, the collapsibility and volume change of partially saturated soils in connection with the drying or wetting causes a lot of damage to foundation, roads and other structures. As such, the development of extended soil mechanics, which embraces the soil in the unsaturated state or subjected to soil suction, is essential. This paper examines the collapsibility and volume change behavior specifically of an unsaturated residual soil under various levels of applied matric suction (ua-uw), and net mean stress (σ-ua) in a predetermined stress path. The volume change of the soil is found to be sensitive to both the applied matric suction and net mean stress. The soil is found to exhibit a collapsibility behavior upon a reduction in applied matric suction to 25 kPa at constant net mean stress.